A Synchronous IRF4-Dependent Gene Regulatory Network in B and Helper T Cells Orchestrating the Antibody Response. Issue 7 (July 2020) - Cook, Sarah L.; Franke, Marissa C.; Sievert, Evelyn P.; Sciammas, Roger
Abstract : Control of diverse pathogens requires an adaptive antibody response, dependent on cellular division of labor to allocate antigen-dependent B- and CD4 + T-cell fates that collaborate to control the quantity and quality of antibody. This is orchestrated by the dynamic action of key transcriptional regulators mediating gene expression programs in response to pathogen-specific environmental inputs. We describe a conserved, likely ancient, gene regulatory network that intriguingly operates contemporaneously in B and CD4 + T cells to control their cell fate dynamics and thus, the character of the antibody response. The remarkable output of this network derives from graded expression, designated by antigen receptor signal strength, of a pivotal transcription factor that regulates alternate cell fate choices. Highlights: The antibody response is orchestrated by the development of distinct B- and CD4 + T-cell fates with specialized function. Distinct B- and CD4 + T-cell fates are controlled by an antigen receptor signal strength-responsive, incoherent gene regulatory network (determined in mice). The transcription factor IRF4 is a central and essential node of this network, whose expression scales with the intensity of antigen receptor signal strength. Graded expression and differential DNA affinity of IRF4 can function to control the outcome of counter-antagonistic gene regulatory interactions governing alternate cell fates.